Looking at OER with a Critical Eye: Strengthening OER Initiatives by Focusing on Student Learning. Issue 1 (2nd April 2016) - Pierce, Matthew
ABSTRACT: This paper discusses aspects of adopting, adapting, and building Open Educational Resources (OER) that have the potential to influence student learning but are sometimes overlooked by OER advocates. The author makes recommendations for ensuring that OER initiatives have a positive impact on student learning and argues that librarians can be effective advocates for student learning by taking a leadership role in the OER discussion on campus.